Pelatihan Technopreneurship Berbasis Digital Bagi Siswa Sekolah Menengah Kejuruan (SMK) - Fitriana Harahap; Wirhan Fahrozi; Elida Tuti Siregar; Nidia Enjelita Saragih; Husin Sariangsah; Robiatul Adawiyah (Universitas Methodist Indonesia, 2026)
The rapid development of digital technology has driven a paradigm shift in entrepreneurship, particularly within vocational education institutions such as Vocational High Schools (SMK). SMK graduates are required not only to possess technical competencies in accordance with their fields of expertise but also to develop technology-based entrepreneurial skills, commonly referred to as technopreneurship. However, limited digital entrepreneurial literacy and a lack of practical experience remain major challenges for SMK students in developing independent technology-based businesses. This community service activity aims to enhance SMK students’ knowledge, skills, and entrepreneurial attitudes through digital-based technopreneurship training. The implementation methods include theoretical lectures, hands-on training in designing digital business ideas, simulations of digital platform utilization, as well as discussions and evaluations. The results indicate an improvement in students’ understanding of technopreneurship concepts, their ability to develop simple digital business ideas, and their motivation to engage in independent entrepreneurship. This activity is expected to serve as a model for strengthening digital entrepreneurship competencies in vocational high schools and to contribute to the preparation of adaptive, innovative, and competitive graduates in the era of digital transformation.